STRATEGI BADAN PERTANAHAN NASIONAL KOTA PEKANBARU DALAM MENCEGAH DAN MENYELESAIKAN KASUS PERTANAHAN DI KOTA PEKANBARU TAHUN 2021-2022 - Varizal, Yuda; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Land dispute management is one of the main challenges in the administration of land affairs in Indonesia, including in the city of Pekanbaru. This thesis aims to analyze the strategy made by the National Land Agency (Badan Pertanahan Nasional/BPN) of Pekanbaru City in preventing and resolving land-related cases during the 2021–2022 period. The research method used is descriptive qualitative, with data collected through interviews, documentation, and literature studies. The findings show that BPN Pekanbaru City has implemented several strategies to prevent and resolve land disputes, including technological strategies, innovation strategies, and operational strategies. These efforts include preventive measures such as the socialization of the Complete Systematic Land Registration (PTSL) program, improving service transparency, and strengthening the land data system. In terms of dispute resolution, BPN plays a role through mediation, document clarification, and collaboration with related institutions such as local governments and law enforcement agencies. Nevertheless, there are still several challenges, such as overlapping data, weak inter-agency coordination, and limited human resources. This study concludes that although the efforts made by BPN Pekanbaru City are in accordance with applicable regulations, strengthening systems and cross-sectoral synergy is necessary to ensure more effective and sustainable land dispute management. Keywords: BPN, Land Administration, Land Dispute, Mediation, Pekanbaru